P104 FEASIBILITY AND ROLE OF ECHOCONTRAST EVALUATION IN PATIENTS WITH LVAD. (18th May 2022) - Baroni, G; Pergola, V; Dellino, C; Aruta, P; Cecchetto, A; Baritussio, A; Fiorencis, A; Di Michele, S; Mastro, F; Tarzia, V; Gerosa, G; Iliceto, S; et al.
Abstract: Background: Advanced heart failure is a clinical syndrome characterized by persistent or progressive symptoms of heart failure despite optimal medical therapy. Left ventricular assist device (LVAD) brings survival benefits and improvement in quality of life, compared with conventional medical treatments. Development of Right ventricle failure in patients with LVAD has a direct effect on mortality and hospitalization. Purpose: evaluation of clinical safety and feasibility of echocontrast in patients implanted with 3 different types of LVAD; improvement in the visualization of heart structures; intra and inter–operator agreement of RV assesement with and without contrast. Methods 43 patients were implanted with LVAD, 7 patients (16%) with Jarvik 2000, 31 (72%) with HeartMAte 3, 5 (12%) with (HeartWAre HVAD). Nine patients (21%) had contraindication or refused contrast. In 3 (7%) patients was technically challenging to obtain apical images at all levels. Two (5%) patients lost their follow–up. Our final population was of 29 (67%) patients (mean age 65±7 y; 100% Male). We assessed the reproducibility of these measurements between two different expert blind operators Results: Total 329 (64%) of 516 RV wall segments were available for qualitative analysis without contrast vs 451 (87%) with contrast (p < 0.001) with a significant improvement of the evaluability of regional contractility (especially due to the better evaluation of medial and apical segments of lateral and anterior walls) and FAC (41% vs 90%, p < 0.001). Evaluation of TAPSE, TR and sPAP was similar with and without contrast (p=NS). All the RV parameters showed little inter–operator variability when measured with contrast. TAPSE, FAC, and RWMA showed an excellent reproducibility (ICC >0.86) while it was good for 2D–baseline derived parameters (ICC = 0.74) showing improvement of inter operator reproducibility in the evaluation of regional contractility in the contrast echocardiography modality. Conclusion: EC is safe with all the types of LVAD examined. Accurate and reproducible visualization of RV is imperative for reliability of information, a routine use of EC could play a pivotal role in interpreting RV features. EC improves RV morphologic and functional judgment allowing greater accuracy and precision in the assessment of both global and regional RV functions. This finding may have important clinical improvement, especially in the future for analysis focused in RV prognostic role in LVAD patients.